How Manufacturers Haste and Consumers Taste Turn into Environmental Waste: a Waste Analysis of Picnickers in Eski?ehir, Turkey - Taslacı, Nazmi; Sarı, Yaşar; Uysal, Davut (European Journal of Economics and Business Studies, 2016)
Since the modern life in the urban areas is fast and exhausting, people who are tired of the routine city life tend to involve in the recreational activities provided by the local governors in their neighborhood. One of these facilities is having a picnic in the picnic areas in the countryside. However, the expansion of these services produces great amount of rubbish and lacks of proper environmental management, too. This study presents an analysis of the waste generated by the visitors in the picnic areas of Eski?ehir in Turkey. Based on observations in various different picnic areas, this study highlights the unsatisfactory aspects of the present situation in terms of the amount and the composition of the picnic waste scattered around. There is also a concern over the expansion of picnic activities in the area that would result in more waste being generated. The characteristics of domestic waste and people’s environmental awareness were studied by observing picnickers and analyzing over lefts they left in the picnic areas. The results showed that the wastes analyzed get accumulated in such categories like chicken packages, bottles, plastic bags, wet towels, diapers and cigarette butts. The motives that drive visitors to be ignorant about their wastes were laziness, carelessness, being accidental and unconsciousness. Therefore, both manufacturers and consumers need to be responsible for this environmental pollution in the picnic areas. Besides educating people about the issue in alternative ways, it is further suggested that governors must make manufacturers feel the need to touch a raw nerve by redesigning their products, and organizing social responsibility facilities and taxing products which are the most frequently found as waste in the recreational areas.
Keywords: manufacturers, consumers, environmental wasre, turkey